The use of platensimycin and platencin to fight antibiotic resistance - Allahverdiyev, Adil M.; Bagirova, Melahat; Abamor, Emrah Sefik; Ates, Sezen Canim; Cakir Koc, Rabia; Miraloglu, Meral; Unal, Gokce (My University, 2013)
Infectious diseases are known as one of the most life-threatening disabilities worldwide. Approximately 13 million deaths related to infectious diseases are reported each year. The only way to combat infectious diseases is by chemotherapy using antimicrobial agents and antibiotics. However, due to uncontrolled and unnecessary use of antibiotics in particular, surviving bacteria have evolved resistance against several antibiotics. Emergence of multidrug resistance in bacteria over the past several decades has resulted in one of the most important clinical health problems in modern medicine. For instance, approximately 440,000 new cases of multidrug-resistant tuberculosis are reported every year leading to the deaths of 150,000 people worldwide. Management of multidrug resistance requires understanding its molecular basis and the evolution and dissemination of resistance; development of new antibiotic compounds in place of traditional antibiotics; and innovative strategies for extending the life of antibiotic molecules. Researchers have begun to develop new antimicrobials for overcoming this important problem. Recently, platensimycin - isolated from extracts of Streptomyces platensis - and its analog platencin have been defined as promising agents for fighting multidrug resistance. In vitro and in vivo studies have shown that these new antimicrobials have great potential to inhibit methicillin-resistant Staphylococcus aureus, vancomycin-resistant enterococci, and penicillin-resistant Streptococcus pneumoniae by targeting type II fatty acid synthesis in bacteria. Showing strong efficacy without any observed in vivo toxicity increases the significance of these antimicrobial agents for their use in humans. However, at the present time, clinical trials are insufficient and require more research. The strong antibacterial efficacies of platensimycin and platencin may be established in clinical trials and their use in humans for coping with multidrug resistance may be allowed in the foreseeable future. © 2013 Allahverdiyev et al, publisher and licensee Dove Medical Press Ltd.
Keywords: Antibiotics; Bacterial infections; Drug resistance; Platencin; Platensimycin